Government Awareness Review: The Form of Parliament's Accountability for the 17+8 Demands as a Form of Accelerating Public Solidarity - Amaliya, Fadhilatul; Pembayun, Dewi Sekar; Roozan, Tiara Jelita Andalusianti; Aequo, Najwa Justitia; Fathiya, Anindya Rahma (International Journal of Law, Crime and Justice, 2025)
The 17+8 demands voiced by the public reflect the accumulation of disillusionment with various government policies and violations committed, especially by the House of Representatives (DPR). Policies that are considered unfair and detrimental to the public trigger a strong push to carry out reforms that are more democratic and oriented towards the interests of the people. Various factors such as human rights violations, lack of transparency and accountability, economic inequality, and polemics related to official allowances are the main triggers for the birth of these demands. The demands of 17+8 not only contain burdens or criticisms, but also contain short-term and long-term goals that can be the basis for improving governance. This momentum should be seen as a strategic opportunity to strengthen democracy, improve state-citizen relations, and restore public trust. If these demands are taken seriously, the government has the potential to reduce the legitimacy crisis and improve the quality of public services. On the contrary, ignoring such demands can deepen public distrust and worsen political stability. Thus, the demands of 17+8 are an important signal for the need for structural change and a real commitment to realizing a fairer, more transparent, and responsive government.